Computo, ergo sum. (Economist, 2026)
The article focuses on how the rise of artificial intelligence is reversing long-held assumptions about career security, with programmers now feeling more threatened by automation than humanities graduates. Topics include the shifting job market dynamics between technical and non-technical fields, the unexpected employability of philosophy graduates compared with some STEM peers, and the growing uncertainty over which skills will remain resilient in an AI-driven economy.